2013
DOI: 10.1089/thy.2012.0401
|View full text |Cite|
|
Sign up to set email alerts
|

Gestational Hypothyroidism Increases the Severity of Experimental Autoimmune Encephalomyelitis in Adult Offspring

Abstract: These results show for the first time that a deficiency in maternal thyroid hormones during gestation can influence the outcome of a central nervous system inflammatory disease, such as EAE, in their offspring. These data strongly support evaluating thyroid hormones in pregnant women and treating hypothyroidism during pregnancy to prevent increased susceptibility to inflammatory diseases in the central nervous system of offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
(51 reference statements)
2
20
0
Order By: Relevance
“…Albornoz et al demonstrated the impact of maternal THs deficiency during gestation on the outcome of offspring central nervous system (CNS) in response to autoimmune inflammatory encephalomyelitis disease. 16 Their animal study suggests that gestational hypothyroidism modulates the offspring immune system in a way that increases the likelihood of the offspring to suffer from severe autoimmune inflammatory diseases in the CNS. 16 In another study, Nieto et al evaluated whether adult mice gestated in hypothyroid mothers display an altered response to pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albornoz et al demonstrated the impact of maternal THs deficiency during gestation on the outcome of offspring central nervous system (CNS) in response to autoimmune inflammatory encephalomyelitis disease. 16 Their animal study suggests that gestational hypothyroidism modulates the offspring immune system in a way that increases the likelihood of the offspring to suffer from severe autoimmune inflammatory diseases in the CNS. 16 In another study, Nieto et al evaluated whether adult mice gestated in hypothyroid mothers display an altered response to pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…16 Their animal study suggests that gestational hypothyroidism modulates the offspring immune system in a way that increases the likelihood of the offspring to suffer from severe autoimmune inflammatory diseases in the CNS. 16 In another study, Nieto et al evaluated whether adult mice gestated in hypothyroid mothers display an altered response to pneumococcal pneumonia. 17 They observed that female mice exposed in utero to maternal hypothyroidism had higher survival rates and fewer bacterial dissemination following an intranasal challenge with Streptococcus pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these TH-stimulated OPCs differentiate into myelinating oligodendrocytes (OLs) to repair demyelinated axons. Through this effect, TH may promote remyelination and contribute to the suppression of MS deterioration significantly impact the CNS by altering the migration, differentiation, and function of OLs [93]. Moreover, an example of hyperthyroidism that initially induces the accelerated maturation process, including cell migration and differentiation, extension of dendritic processes, and synaptogenesis, implicates the effects of TH on cell migration and differentiation [94,95].…”
Section: Thyroid Hormone Activates Oligodendrocyte Precursor Cells Tomentioning
confidence: 99%
“…In susceptible individuals, immune tolerance shaped by self-antigens recognition may fail, leading to a harmful autoimmune response (Shum et al 2009). Unfortunately, up to date the etiology for many autoimmune diseases remains unknown, but a number of studies have suggested that these ailments are strongly associated with factors such as genetics, hormonal status, infections and/or environment factors (Albornoz et al 2013;Bentham et al 2015;Luo et al 2011). The fact that systemic lupus erythematosus (SLE), as well as other autoimmune diseases, preferentially affects women over male would suggest that the female hormonal status could play a pivotal role during autoimmunity onset and progression (Whitacre et al 1999).…”
Section: Introductionmentioning
confidence: 99%